Case Report: Thalassemia with Malnutrition - Budi Arifianto (Faculty of Medicine, Public Health, and Nursing, 2019)
A 2 years old patient presented with a complaint of weight that had not increased in the past few months. The patient was identified by the Puskesmas Team in an integrated UKM activity on March 30, 2017, with a condition of complaining of fever and being taken to the local midwife, but there had been no improvement. Next, after the examination, the patient was advised to be referred to Sukadana Regional Hospital, East Lampung Regency, Lampung, where physical and laboratory examinations were conducted with results showing hemoglobin (Hb) 6.9 and a pediatrician established a diagnosis of thalassemia.